Entrepreneurs as intermediaries - Peng, Mike; Lee, S.; Hong, S. (Pergamon, 2014)
This paper sketches the contours of a theory of entrepreneurship focusing on the nature of entrepreneurship as intermediation under information asymmetries. While entrepreneurship, strategy, and finance researchers have studied the relationship between entrepreneurs and intermediaries, they tend to treat intermediaries, such as venture capitalists, as a separate organizational form that is parallel with (start-up) entrepreneurs. In this paper, we consider entrepreneurs as intermediaries who discover, create, and exploit entrepreneurial opportunities by bearing uncertainties stemming from intermediation between potential buyers and sellers under information asymmetries. Specifically, we focus on two key questions in entrepreneurship research: (1) Why do entrepreneurs arise and exist at all? (2) Why do some entrepreneurs perform better than others in creating entrepreneurial opportunities and ultimately creating wealth? Our discussion culminates in a new research agenda with four testable propositions.